A DFT study of electronic, magnetic, optical and transport properties of rare earth element (Gd, Sm)-doped GaN material. (1st March 2022) - Maskar, E.; Lamrani, A. Fakhim; Belaiche, M.; Es-Smairi, A.; Vu, Tuan V.; Rai, D.P.
Abstract: The main objective of this article is to deal with and establish a new type of transparent conducting material by doping Gallium Nitride (GaN) with rare-earth RE (Gd, Sm) elements. A theoretical study was performed by using the density functional theory (DFT) implemented in WIEN2k code and BoltzTraP package based on semi-classical Boltzmann transport equation (BTE) within constant relaxation time and rigid band approximation (RBA). The application of the modified Becke–Johnson (TB-mBJ) potential has improved the electronic structure, especially the electronic bandgap. Our simulation result matches with other computational results as well. We have compared the total energy of ferromagnetic (FM) and Anti-ferromagnetic (AFM) configurations for the doped system to analyze the magnetic ground state stability. Preferentially the most stable magnetic configuration is found to be ferromagnetic. The low value of formation energy indicates the possibility of the preparation of these materials in the lab. To further compare the results, we have also used the VNL-ATK quantumwise code based on the Linear Combination of Atomic Orbital (LCAO) approach. VNL-ATK incorporate a new functional DFT-1/2 to correct the Kohn–Sham KS eigenvalues around the minima and maxima of the conduction band, and the valence band, respectively, which enhances the bandgap. It shows the high optical absorption and the high electrical conductivity. These characteristics offer that GaN doped with rare earth elements are potential candidates for optoelectronic, solar cell, and spin-based magnetic devices.